2019
DOI: 10.1007/s40119-019-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-Term Outcomes of Patients with Impaired Left Ventricular Systolic Function Undergoing Rotational Atherectomy: A Single-Center Observational Retrospective Study

Abstract: IntroductionRotational atherectomy (RA) historically was contraindicated in patients with impaired left ventricular (LV) function due to inherent cardio-depressive effects. Contemporary RA practice is less aggressive than traditional RA and no longer withheld from patients with reduced ejection fraction (EF). The aim of this analysis is to explore the outcomes of rotational atherectomy (RA) in patients with reduced left ventricular ejection fraction (LVEF).MethodsPatients undergoing RA (n = 644) were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…There may be a significant effect of RA surgery on microvascular function, which is likely to irreversibly induce myocardial damage and reduced ventricular function, ultimately leading to significant differences in long-term prognoses. [29] However, other factors may be involved in the development of MACE, and studies by Watanabe Y, Chen, Cilia L, and others suggest that MACE incidence is similarly high in patients with RA showing renal insufficiency and low EF,[3538] and therefore, the results need to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a significant effect of RA surgery on microvascular function, which is likely to irreversibly induce myocardial damage and reduced ventricular function, ultimately leading to significant differences in long-term prognoses. [29] However, other factors may be involved in the development of MACE, and studies by Watanabe Y, Chen, Cilia L, and others suggest that MACE incidence is similarly high in patients with RA showing renal insufficiency and low EF,[3538] and therefore, the results need to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis demonstrates higher rates of in-hospital TVR in the groups with severely reduced LVEF while the long term TVR rates were not different between the two groups. One study showed that TVR rates at 5 years were not affected by LVEF ( 13 ). In ORBIT II, the rate of 1-year TVR was comparable across the LVEF groups ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In two other studies by Watanabe et al [ 90 ] and Whiteside et al [ 91 ], slow flow was significantly higher in severely-reduced LVEF patients (defined as ≤ 35% by Watanabe et al and as ≤ 30% by Whiteside et al). A recent study found slow flow to be more than fivefold higher in patients with severely reduced LVEF (≤ 35%) as compared to preserved LVEF (≤ 55%) [ 92 ]. In another analysis done by Mankerious et al patients with severely reduced LVEF had worse acute outcome after RA as well as higher mortality on long term [ 92 ].…”
Section: Patients and Lesions Treated With Ra In The Current Practicementioning
confidence: 99%
“…A recent study found slow flow to be more than fivefold higher in patients with severely reduced LVEF (≤ 35%) as compared to preserved LVEF (≤ 55%) [ 92 ]. In another analysis done by Mankerious et al patients with severely reduced LVEF had worse acute outcome after RA as well as higher mortality on long term [ 92 ].…”
Section: Patients and Lesions Treated With Ra In The Current Practicementioning
confidence: 99%